A model for Rab GTPase localization. (1st August 2005) - Pfeffer, S.
Abstract : The human genome encodes almost 70 Rab GTPases. These proteins are C-terminally geranylgeranylated and are localized to the surfaces of distinct membrane-bound compartments in eukaryotic cells. This mini review presents a working model for how Rabs achieve and maintain their steady-state localizations. Data from a number of laboratories suggest that Rabs participate in the generation of macromolecular assemblies that generate functional microdomains within a given membrane compartment. Our data suggest that these complex interactions are important for the cellular localization of Rab proteins at steady state.